The methylome of the hypothalamus of prepubertal and pubertal goats. (International Journal of Health, Animal Science and Food Safety, 2016)
Puberty is the fulfillment of fertility, a process involving physiological and morphological development.It is well known that the increased hypothalamic secretion of the gonadotropin-releasing hormone(GnRH) is essential for the activation of this process, even if the elements coordinating the timing ofpuberty have not been fully identified1,2. Recent studies provide proof that there is an epigeneticregulation of female puberty, and DNA methylation, the most studied epigenetic modification, plays amajor role in it3. We analyzed DNA methylation patterns of 5 Alpine goats at their prepubertal stageand 5 that reached puberty in order to highlight differences in their methylome. Detection ofmethylated regions across the goat genome involved a Methyl Binding Domain (MBD) enrichmentfollowed by deep sequencing (Hiseq2000 Illumina). The software ChIPseeqer4 permitted theidentification of peaks corresponding to hyper-methylated regions. We have observed a highermethylation level in prepubertal goats. The distribution of the methylation peaks across the genomeand within CpG islands per chromosome per group of animals has been analyzed. Furthermore, we haveinvestigated differential methylation in genes associated with puberty. Specifically, Cbx7, coding for acore component of the Polycomb group silencing complex, and GnRHR, the gene coding for GnRHreceptor, showed a higher number of peaks into two intragenic fragments within prepubertal goats.These results, accompanied by transcriptome analysis, provide a foundation for elucidating the role ofDNA methylation in the complex mechanisms that drive puberty in goat species.
Keywords: goat; methylation; puberty